Adult Type Chronic Myeloid Leukaemia in An 11 Year Old Girl- A Very Unusual Case Report (Bangladesh Journal of Medicine, 2015)
Chronic Myeloid Leukaemia is very uncommon in children. It accounts for 2 to 5% of all the childhood leukaemias. The incidence is < 1 case per 1,00,000 population in younger than 20 years of age per year. Two distinct forms have been described- namely the Juvenile and Adult type. Absence of Philadelphia chromosome is the hallmark of Juvenile type CML ( JCML). Adult type CML is extremely rare in childhood. Here, we report one such a case of adult type of CML in an 11 year old girl who presented to us with pallor, fever and hepato-splenomegaly. At presentation, it seems to be a case of Visceral Leishmaniasis. But, peripheral blood film and bone marrow features were consistent with CML. Philadelphia chromosome was positive. Though biological behavior and prognosis are identical to that of adult CML, we are reporting this case because of its extremely uncommon incidence.Bangladesh J Medicine Jul 2014; 25 (2) : 72-75